3D cell technology in biomedical research - Mišković Špoljarić, Katarina (Array, 2020)
Traditional two dimensional cell culture has enabled great strides in biomedicine but needs to be improved to be able to keep up with the demands of modern biomedical research. 2D monolayer culture cannot replicate tissue responses and needs to be supplemented with extensive animal research. Growing cells in three dimensional scaffolds provides a more functional model for biomedical research than traditional monolayer culture. Depending on the needs and the complexity of the model there are several ways that 3D models can be initiated. Simple spheroids can be grown in low adherence plates and in hanging drops while larger spheroids and co-cultured ones need to be grown in systems with greater support such as hydro gels. The system that offers the greatest flexibility is the magnetic levitation approach. In the paper we offer a brief resume to various 3D methods and their characteristics to ease the choice of methods for implementing 3D cell culture techniques.